Cassava (Manihot esculenta Crantz) stump biochar: Physical/chemical characteristics and dye affinity. Issue 7 (3rd July 2019) - Meili, L.; Godoy, R. P. S.; Soletti, J. I.; Carvalho, S. H. V.; Ribeiro, L. M. O.; Silva, M. G. C.; Vieira, M. G. A.; Gimenes, M. L.
Abstract: Aiming investigated the pyrolysis of the agricultural waste known as cassava stump, the portion of the plant to which the tuberous roots and aerial parts of the plant are attached, this study had as objective to produce biochars from cassava stump by conducting vacuum pyrolysis at 400, 500, or 600 °C. The biochars were characterized by proximate analysis, thermogravimetric analysis, Fourier-transform infrared absorption spectroscopy, X-ray diffraction, scanning electron microscopy, and nitrogen adsorption. Adsorption affinity tests were performed with four different dyes: methylene blue, basic fuchsin, acid fuchsin, and alizarin. Biochar obtained at 500 °C, heating rate of 20 °C.min −1, and 90 min of residence at the final temperature, had 22% higher fixed carbon content as compared to the other biochars and 3.16 times greater fixed carbon content than the original cassava stump. This biochar showed the best adsorption capacity (0.0679 mmol/g) and percentage of removal (87.6%) of methylene blue dye from aqueous solution. The material characterization reveals that biochars from Manihot esculenta Crantz stump may have potential application in carbon sequestering. Besides that, these biochars could be applied with efficiency as adsorbent of dyes.